Jual Beli Hak Atas Tanah Berdasarkan Hukum Adat di Desa Abiansemal - Dewa Made Yudiartha Prayogi; I Made Suwitra; Ni Gusti Ketut Sri Astiti (Jurnal Interpretasi Hukum, 2022)
Land has a very important value in people's lives because it is synonymous with the survival of a society. In Bali, especially in the traditional village of Abiansemal, there are still those who are in the process of buying and selling land certificates related to the transfer of rights, in relation to the processes and procedures regulated in Abiansemal's settlements in ordinary villages. The lease is settled on land in the usual Abiansemal village area. This paper discusses the sale and purchase of land rights according to customary law in Abiansemal village. This study uses empirical legal research with a legal and conceptual approach. Data collection techniques used are observation, interviews, and documentary studies. The results of this study note that the procedures and legality of buying and selling land ownership according to customary law in Abiansemal Village are regulated in the Abiansemal Village Regulation and State Administrative Regulations concerning the Transfer of Rights and Land Leases in the Abiansemal Village Area, UUPA, namely PP No. 24 people since 1997.